Bacteriological analysis of donor human milk in milk bank in an Indian setting - Singh, Poonam H; Surana, Amita Uday; Chaudhari, Vaishali (Indian Journal of Child Health, 2017)
Background: Although human milk banking in India was started in 1984, limited data regarding bacteriological quality of milk are available. Objective: To find bacteriological contamination of milk samples in human milk bank. Methods: Retrospective analysis of milk samples from milk bank for the year 2009-2015 was done. Group A donor mothers were from postnatal or neonatal units of our hospital. Group B mothers were from milk donation camps organized at the community level. All milk samples were plated on blood agar for bacteriological analysis. Pre-pasteurized samples were analyzed for the year 2014-2015 only. Results: Total donor mothers were 3670. 1481 (40%) were from milk donation camp at the community level. 327 (9%) were preterm milk. 2.34% of post-pasteurized samples showed contamination as compared to 9.1% pre-pasteurized milk samples (p=0.002). Group A mothers showed a higher contamination rate as compared to Group B mothers in both pre-pasteurized (p